Modeling water supply and demand scenarios: the Godavari-Krishna inter-basin transfer, India - Bharati, Luna; Smakhtin, Vladimir U.; Anand, B.K. (IWA Publishing, 2009)
The Government of India's National River-Linking Plan (NRLP) aims to alleviate emerging water scarcity problems by transferring water from well endowed to more deficient areas. This study evaluated the plausible future scenarios of water availability and use under conditions of various cropping patterns, and with the explicit inclusion (for the first time) of environmental water requirements for one of the links of the NRLP: from the Godavari River at Polavaram to the Krishna River at Vijayawada?the 'Polavaram Project'. The scenarios were evaluated using the WEAP (Water Evaluation and Planning) model. The study generates information for use in managing emerging trade-offs. The importance of explicit accounting for monthly variability in description of water supply and demand, in the monsoon-driven climate conditions of the region, is advocated. Such detailed scenario simulations and inclusion of previously unaccounted for factors/uses can help to create awareness of potential future problems, inform water management practices and suggest management alternatives. Results show that the proposed water storage and transfer will reduce water deficit within the project command area and significantly reduce dry slow river flow into the Lower Godavari Delta.